Simulasi Finite Element Method Pada Komposit Berbasis Aluminium Hasil Accumulative Roll Bonding (ARB) Dengan Penambahan Pressing (Tekanan) - Pramono, Agus; Zulfia, Anne (ROTASI, 2020)
The technology of severe plastic deformation (SPD) consists of several types on processes, the most well-known on the processes are three types, namely; equal channel angular pressing (ECAP), high pressure torsion (HPT) and accumulative roll bonding (ARB). SPD technology was developing rapidly as metal and alloy processing. At present, the SPD has been used for the development of composite materials. To produce high mechanical properties in SPD requires a long pressure cycle. To analyze the accuracy of the process variables the temperature simulation, pressing and rolling pressures were performed, using the finite element method (FEM). The simulation was done by used of ANSYS 2019 R3 software type. The simulation traces the accuracy of the heating distribution due to thermal stress, pressing and rolling pressures, so that the ideal parameter values in the process are known. Simulation used ANSYS software. The temperature used in this simulation process is 377oC with a time of 2 hours. While the press pressure applied at 1700 N is equivalent to 0.173352 tons and the maximum rolling load capacity of 60 tons is equivalent to 588399 Newton.Â Teknologi severe plastic deformation (SPD) terdiri dari beberapa jenis proses, proses yang paling terkenal ada tiga jenis yaitu; equal channel angular pressing/ECAP, high pressure torsion/HPT dan accumulative roll bonding/ARB. Teknologi SPD berkembang pesat sebagai pemrosesan logam dan paduan. Saat ini SPD telah digunakan untuk pengembangan material komposit. Untuk menghasilkan sifat mekanik yang tinggi pada SPD diperlukan siklus tekanan yang panjang. Untuk menganalisis ketepatan varibel proses maka dilakukan simulasi tempreratur, tekanan pressing dan rolling, menggunakan finite element method (FEM). Simulasi dilakukan dengan menggunakan jenis software ANSYS 2019 R3. Simulasi menelusuri ketepatan distribusi pemanasan akibat tegangan thermal, tekanan pressing dan rolling, agar diketahui batasan nilai parameter yang ideal pada proses. Simulasi menggunakan software ANSYS. Temperatur yang digunakan pada proses simulasi ini adalah sebesar 377oC dengan waktu selama 2 jam. Sedangkan tekanan press diterapkan 1700 N setara dengan 0.173352 ton dan tekanan rolling kapasitas maksimum bebannya sebesar 60 ton setara dengan 588399 Newton.